Judicial Corruption Between Community Legal Culture And Government Administrative Legal Violence - Eman Suparman (Legal Standing : Jurnal Ilmu Hukum, 2017)
This Research focus in Judicial Corruption between community. This research as kualitative descriptive, Based on the description discussed in introduction and discussion section, there are some conclusion that can be drawn as follows: According to the examples given, it is true that judicial corruption that involves government officers occurs in the judiciary institutions. Based on the result of observation, it is found that judicial corruption does not only performed by government officers, but it also involves other parties, in this case; advocates and defendants. Essentially, judicial corruption behavior is also influenced by people’s misconception of legal culture. As the justiciabelen or the seeker of justice, what is perceived by people is to win the civil case, or not to be imprisoned for criminal case. Therefore, this kind of legal culture always uses economic approach. It is true that one of factors that influence the judicial corruption is the violation of government administration law. In this case, such violation is performed by the government officers that are assisted by the advocates altogether.